2010
DOI: 10.4061/2010/131630
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage Stresses Generated during Resin-Composite Applications: A Review

Abstract: Many developments have been made in the field of resin composites for dental applications. However, the manifestation of shrinkage due to the polymerization process continues to be a major problem. The material's shrinkage, associated with dynamic development of elastic modulus, creates stresses within the material and its interface with the tooth structure. As a consequence, marginal failure and subsequent secondary caries, marginal staining, restoration displacement, tooth fracture, and/or post-operative sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
139
0
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 110 publications
(151 reference statements)
3
139
0
19
Order By: Relevance
“…Polymerization shrinkage of resin composites may be a potentially harmful factor for the clinical survival of direct restorations as a result of the transfer of stresses to the adhesive interface. 35 Ideally, marginal adaptation, which depends on polymerization shrinkage and resulting stress, should be assessed at baseline because both shrinkage and resulting stress take place during the placement of the restoration. Other clinical factors, such as wear and the integrity of the adhesive interface, may have induced changes in marginal adaptation over the one year of clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Polymerization shrinkage of resin composites may be a potentially harmful factor for the clinical survival of direct restorations as a result of the transfer of stresses to the adhesive interface. 35 Ideally, marginal adaptation, which depends on polymerization shrinkage and resulting stress, should be assessed at baseline because both shrinkage and resulting stress take place during the placement of the restoration. Other clinical factors, such as wear and the integrity of the adhesive interface, may have induced changes in marginal adaptation over the one year of clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several attempts to overcome polymerization shrinkage such as using an incremental layering technique, placing a stress-absorbing liner, and changing the light-curing procedures. 1,2 Recently, a silorane-based material was introduced. Silorane composite has shown approximately 0.94 vol% to 1.5 vol% shrinkage [3][4][5] and comparable flexural strength to methacrylate composite.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, no single method has been totally efficacious in counteracting the effects of polymerization shrinkage. 15 In all the groups, the gap width decreased from the outer part of the cervical margin to the inner part which represents a V-shaped gap formation in composite restorations on root surfaces. It has been reported that this phenomenon occurs because polymerization shrinkage forces are greater than the initial bond strength of composite to root dentin.…”
Section: Discussionmentioning
confidence: 99%